Genetic differentiation in species of Anopheles from the subgenera Nyssorhynchus based on mitochondrial DNA - Borges-Moroni, R.; Fraga, Elmary da Costa; Maia, Juracy de Freitas; Tadei, Wanderli Pedro; Santos, Joselita Maria M. (Open Tropical Medicine Journal, 2012)
Our group analyzed species of Anopheles of the subgenus Nyssorhynchus (An. darlingi, An. marajoara, An. oswaldoi, An. benarrochi, An. triannulatus and An. rangeli) and a single species of the subgenus Anopheles (An. mattogrossensis), originating in the Amazon, based on the mitochondrial DNA control region. The fragment had 381 pb and the nucleotide composition in A+T ranged from 85.8 to 89.5%. DNA polymorphism analysis of the species detected 15 haplotypes, with the presence of 81 polymorphic loci, 95 mutations, haplotypic divergence of 0.879, nucleotide diversity of 0.06507, nucleotide differences pair the pair mean of 23.1749, and the observed and expected variances of 113.840 and 8.33, respectively. The genetic distance among the Anopheles species varied from 0.06 to 1.37%. An. oswaldoi and An. rangeli were the most similar, with nucleotide divergence of 0.17%. The An. benarrochi populations of Ji-Paraná and Bolivia showed nucleotide divergence of 0.06%. An. darlingi, An. marajoara and An. triannulatus presented nucleotide divergences of 0.35% between An. triannulatus and An. darlingiand of 0.47% between An. darlingi and An. marajoara. This data showed ample interspecific nucleotide variation, though with low nucleotide divergence. The cladogram separated the species of the subgenus Nyssorhynchus and those of the subgenera Cellia and Anopheles, with 98% bootstrap. The region control data did not show strong phylogenetic support, as indicated by the transition/transversion mean rate (0.4643), which is necessary for increasing fragment size and using other more conservative genes for greater inference concerning the phylogeny of the Anopheles species of the subgenus Nyssorhynchus. © Borges-Moroni et al.
Keywords: Dna, Mitochondrial; Anopheles; Anopheles Benarrochi; Anopheles Darlingi; Anopheles Marajoara; Anopheles Mattogrossensis; Anopheles Oswaldoi; Anopheles Rangeli; Anopheles Triannulatus; Cellia; Controlled Study; Dna Polymorphism; Gene Mutation; Genetic Distance; Genetic Variability; Genus; Haplotype; Nonhuman; Nucleic Acid Base Substitution; Nyssorhychus; Phylogeny; Polymorphic Locus; Priority Journal; Species Difference; Species Identification